Lactose and major milk proteins are present in secretory vesicle-rich fractions from lactating mammary gland. - Sasaki, M (1978)
Preparations enriched in apparently intact secretory vesicles were isolated from homogenates of lactating rat and bovine mammary tissue by differential and density gradient centrifugation in isoosmotic media. Morphologically these preparations consisted nearly entirely of vesicles of varying sizes, at least some of which contained casein micelles. Endoplasmic reticulum vesicles, Golgi apparatus cisterna and dictyosomes, mitochondria, peroxisomes, lysosomes, and nuclei were not observed in secretory vesicle-rich fractions. Vesicle preparations were enriched in lactose relative to total membrane fractions from mammary gland. The galactosyltransferase of lactose synthase (UDPgalactose: D-glucose 4 beta-galactosyl-transferase, EC 2.4.1.22) was also present in secretory vesicle preparations, alphas1- and beta-caseins, alpha-lactalbumin, and beta-lactoglobulin, the major secretory proteins of differentiated mammary epithelial cells, were identified as constituents of vesicle-rich fractions from bovine mammary gland. These observations suggest that the major carbohydrate and major proteins of milk are compartmentalized into secretory vesicles and are secreted by exocytotic fusion of secretory vesicles with the apical plasma membrane.